2006
DOI: 10.2169/internalmedicine.45.1855
|View full text |Cite
|
Sign up to set email alerts
|

Overt Diabetes Mellitus in a Patient with Combined Primary Aldosteronism and Cushing's Syndrome

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many cases of PA with hypercortisolism reported thus far [29][30][31][32][33] are due to a solitary adenoma co-secreting aldosterone and cortisol, as in Cases 1 and 7. However, aldosterone hypersecretion as confirmed by AVS in our 4 patients (Cases 2, 3, 5, 6) was from the contralateral side of the adrenal lesions by imaging side detected by CT imaging in all 8 PA/SCS patients, which is compatible with concomitant cortisol-and/or aldosterone-producing tumors.…”
Section: Discussionmentioning
confidence: 96%
“…Many cases of PA with hypercortisolism reported thus far [29][30][31][32][33] are due to a solitary adenoma co-secreting aldosterone and cortisol, as in Cases 1 and 7. However, aldosterone hypersecretion as confirmed by AVS in our 4 patients (Cases 2, 3, 5, 6) was from the contralateral side of the adrenal lesions by imaging side detected by CT imaging in all 8 PA/SCS patients, which is compatible with concomitant cortisol-and/or aldosterone-producing tumors.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, at least 33 other cases of concurrent autonomous secretion of both aldosterone and cortisol from aldosterone cortisol-producing adenomas (ACPAs) have been reported so far. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Higher expression of mRNA for 17α-hydroxylase has been found in ACPAs compared to APAs. 22 Furthermore, immunohistochemical analysis of ACPAs has shown that aldosterone synthase on the one hand, and both enzymes specifically involved in cortisol biosynthesis (i.e., 17α-hydroxylase and 11β-hydroxylase) on the other hand, are localized in two different cell types; this finding suggests the existence of two separate cell populations with different steroidogenic pathways in ACPAs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described abnormalities in glucose homeostasis and metabolism in patients with PA (12,13,14,15,16,17,18,19,20,21,22); however, they often showed inconsistent results due to limitations in sample size, lacking of a matched control group, or nonstandardized diagnosis of PA. Nevertheless, there is growing evidence that aldosterone is involved in the pathogenesis of insulin resistance and MetS (23,24).…”
Section: Introductionmentioning
confidence: 99%